2018
DOI: 10.1111/1346-8138.14347
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the bactericidal effects of indocyanine green‐ and methyl aminolevulinate‐based photodynamic therapy on Propionibacterium acnes as a new treatment for acne

Abstract: Acne vulgaris is one of the most common dermatological problems, and its therapeutic options include topical and systemic retinoids and antibiotics. However, increase in problems associated with acne treatment, such as side-effects from conventional agents and bacterial resistance to antibiotics, has led to greater use of photodynamic therapy. The purpose of this study was to compare the bactericidal effects of indocyanine green- and methyl aminolevulinate-based photodynamic therapy on Propionibacterium acnes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Nonablative fractional laser treatment was found to assist daylight photodynamic therapy with topical methyl aminolevulinate for moderate to severe facial acne vulgaris . In addition, new photosensitizers, such as indole‐3‐acetic acid and indocyanine green, have been introduced for the treatment of acne vulgaris . In this study, we evaluated photodynamic therapy with a cleanser containing 5‐ALA and peptides for mild to moderate facial acne vulgaris.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonablative fractional laser treatment was found to assist daylight photodynamic therapy with topical methyl aminolevulinate for moderate to severe facial acne vulgaris . In addition, new photosensitizers, such as indole‐3‐acetic acid and indocyanine green, have been introduced for the treatment of acne vulgaris . In this study, we evaluated photodynamic therapy with a cleanser containing 5‐ALA and peptides for mild to moderate facial acne vulgaris.…”
Section: Discussionmentioning
confidence: 99%
“…have been introduced for the treatment of acne vulgaris. 16,17 In this study, we evaluated photodynamic therapy with a cleanser containing 5-ALA and peptides for mild to moderate facial acne vulgaris.…”
Section: Re Sultsmentioning
confidence: 99%
“…Accordingly, researchers have called for limiting the use of oral antibiotics in the treatment of acne. 17 Meanwhile, studies have indicated that plasma holds profound bactericidal and fungicidal properties in vitro, and a prospective randomized controlled trial has shown argon plasma to be efficacious and safe in decreasing bacterial load in chronic wounds. 11,12,18 As seen in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 (2) Grading Scale for overall severity (GSOS) was an evolution of the GAGS, which graded only on the facial area and was applied in the Australia; 13 (3) the US Food and Drug Administration (FDA) and Europe encouraged the Global Assessment of Acne (IGA) and the Global Assessment of Acne (GEA) scale respectively; 14-17 (4) The grading tools used in China were the International Improved Grading System (IIGS) advocated in the textbook of Chinese Clinical Dermatology edited by Zhao Bian and the acne grading system (AGS), which was stated in the Acne Diagnosis and Treatment Guide of China; 17,18 (5) Korea Acne Grading System (KAGS) and Japan Acne Grading System (JAGS) were utilized in Korea and Japan respectively. 19,20 Every AV evaluation tool has benefits and drawbacks. The type and quantity of lesions are considered by GAGS, GOGS, IGA, GEA, IIGS, KAGS, and JAGS except IGA.…”
Section: Introductionmentioning
confidence: 99%